Usage of Social Media in City Marketing: A Research on 30 Metropolitan Municipalities in Turkey - Niyazi Gümüş (University Library System, University of Pittsburgh, 2017)
Rapid changes in information and communication technologies cause serious developments in marketing field similar to every sector. In parallel with these developments, the social media channels which appear as Web 2.0 applications have a number of advantages in comparison with traditional media channels. Social media gained a place in marketing activities because of its advantages. Social media is added on instruments in line with these developments that countries benefit in marketing activities for attracting more tourists, investment and becoming prominent against the other cities. Cities intensively benefit from social media because of social media’s properties like reaching the large masses, low marketing cost, interaction, receiving feedbacks rapidly, etc. Within this context, the purpose of this research is to determine the use statuses of social media by metropolitan municipalities as part of city marketing. In accordance with this purpose, official social media accounts of 30 metropolitan municipalities are investigated between the dates of 01/09/2016 and 30/09/2016, then their shares in social media channels are investigated in the context of city marketing.It is observed that two metropolitan municipalities do not have official Facebook accounts, four metropolitan municipalities do not have an official Twitter account as well. Again, it is found that 19 metropolitan municipalities do not have an official Instagram account and 17 metropolitan municipalities do not have official YouTube account. In consequence, it is observed that, our metropolitan municipalities do not benefit from social media effectively for city marketing activities.
Keywords: Social media; City marketing; HF5001-6182; Management. Industrial management; Business; Metropolitan municipalities; HD28-70